2016
DOI: 10.1016/j.matbio.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of versican expression by siRNA facilitates tropoelastin synthesis and elastic fiber formation by human SK-LMS-1 leiomyosarcoma smooth muscle cells in vitro and in vivo

Abstract: Versican is an extracellular matrix (ECM) molecule that interacts with other ECM components to influence ECM organization, stability, composition, and cell behavior. Versican is known to increase in a number of cancers, but little is known about how versican influences the amount and organization of the ECM components in the tumor microenvironment. In the present study, we modulated versican expression using siRNAs in the human leiomyosarcoma (LMS) smooth muscle cell line SK-LMS-1, and observed the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…This is the first demonstration that a loss of Thbs1 improves the elastic fiber organization in the structurally compromised aortas. Second, it has previously been shown that inhibition of versican, which is a large extracellular matrix proteoglycan, promotes tropoelastin synthesis and elastic fiber formation in human leiomyosarcoma SMCs 48 . Since versican forms a functional complex with Thbs1 and is co-localized on microfibrils 49 , deletion of Thbs1 may have disrupted the inhibitory complex and facilitate elastic fiber formation in DKO aortas.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first demonstration that a loss of Thbs1 improves the elastic fiber organization in the structurally compromised aortas. Second, it has previously been shown that inhibition of versican, which is a large extracellular matrix proteoglycan, promotes tropoelastin synthesis and elastic fiber formation in human leiomyosarcoma SMCs 48 . Since versican forms a functional complex with Thbs1 and is co-localized on microfibrils 49 , deletion of Thbs1 may have disrupted the inhibitory complex and facilitate elastic fiber formation in DKO aortas.…”
Section: Discussionmentioning
confidence: 99%
“…Such a matrix that fails to transit to a more fibrous, cross-linked mature ECM could provide an environment for continued tumor growth, promoting tumor cell proliferation and migration [129]. In cancer, either the stromal cells surrounding the tumor or the tumor cells themselves produce hyaluronan/versican provisional matrices impacting tumor cell proliferation, migration, and metastasis [78, 123125, 131]. For example, in a study of human leiomyosarcoma smooth muscle tumors which are enriched in versican, we found that the tumor cells exhibited thick pericellular coats in culture which could be reduced by inhibiting versican synthesis using siRNA treatment of these cells (Figure 5) [123].…”
Section: Hyaluronan and Versican In Provisional Matrices In Cancermentioning
confidence: 99%
“…While collagen and elastin are the most abundant proteins in the ECM, proteoglycans play an important role in regulating the assembly, organization, and turnover of these proteins. The large chondroitin sulfate proteoglycan Vcan accumulates in tissues during inflammation and injury, where it interferes with elastic fiber assembly 7,8 and disrupts collagen remodeling 9,10 in a number of conditions including liver fibrosis, cancer, and chronic obstructive pulmonary disease. Furthermore, Vcan is emerging as a critical regulator of inflammation and has a major impact on tissue response to injury and disease 11,12 .…”
Section: Introductionmentioning
confidence: 99%